IMPLEMENTATION OF CHARACTER EDUCATION PROGRAM IN ISLAMIC SMP AL AZHAR 21 SOLO BARU - Henni Putri Hernani; Nurul Latifatul Inayati (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
Character education is very important in building superior and strong human resources. Build the positive character are not just forming children into smart and good personalities, but also forming their characters in daily life practices that have an impact on the changing order of society and other people. Each school contributes to make a generation that has good character, both public and private schools that compete in developing the country through the world of education including the Al Azhar 21 Islamic Middle School Solo which has implemented a character education program since it was first established.                 Al Azhar 21 Islamic Junior High School Solo Baru is a superior private school, this school was only established in 2005 and until now has been able to compete and prove the quality of schools by winning various regional and national junior high school competitions. This school uses an integrated character education curriculum, and this school is a reference for comparative studies in character education. The formulation of the problem taken by the researcher is “what is the implementation of the character education program and what are the supporting and inhibiting factors in implementing the character education program in Al Azhar 21 Islamic Junior High School Solo Baru. This Research aims to explain the implementation of character education programs at Al Azhar 21 Middle School and its supporting and inhibiting factors.                 In this study, researchers used a type of field research that was packaged in the form of a phenomenological qualitative research that is research conducted by visiting the research site to conduct direct observations. Data collection used is interview, observation and documentation, which then the data can be analyzed by the deductive method. Deductive method is a processing that starts from the theoretical foundation which is then adjusted to the data obtained in the field. Furthermore, conclusions are drawn with the deductive method of thinking that departs from the theory and then adjusted to the data.                 The results of the study can be concluded that the Al Azhar 21 Islamic Middle School has a work programm (proker) in implementing character education, which is a daily and annual program. This program aims to improve the religious quality of school residents. At Al Azhar 21 Solo Baru Islamic Middle School, there are five values of character education taught every day, namely religious observance, environmental love, responsibility, discipline and courage / confidence. Supporters in the implementation of character programs in Al Azhar are students who have strong criteria to be able enter the Al Azhar school, teachers who must have memorized the Al-Qur’an and are competent and professional in their work, and Al Azhar has an Islamic environment that allows students to learn comfortably. Constraints faced are family: lack of supervision from parents. Because most students who attend Al Azhar are elite people, so that the parents are too busy with their work, an than there is less time to supervise children at home. the influence of association from the environment outside the school due to technology, because the school has difficulty in supervising students when they are already outside school, with this problem the school also provides a solution with the Al Azhar hostel (asrama) for parents who wish their children have a good environment.